A puncturable attribute-based data sharing scheme for the Internet of Medical Robotic Things. Issue 4 (31st August 2021) - Basudan, Sultan
Abstract : Purpose: In line with the fast development of information technology, the Internet of Medical Robotic Things (IoMRT) is gaining more ground in health care. Sharing patients' information effectively and securely can improve sensing data usage and confidentiality. Nevertheless, current IoMRT data sharing schemes are lacking in terms of supporting efficient forward secrecy; when secret key for a robotic nurse as a data requester is compromised, all the historically shared data with this robotic nurse will be leaked. Design/methodology/approach: The presented paper suggests an efficient puncturable attribute-based data sharing scheme enabling guaranteed firm security and versatile access control over health sensing data in IoMRT. This scheme integrates attribute-based and puncturable encryption to avail a shared secret key for data sharing that can be encrypted by an access structure over the Data Requester (DR) attributes. Additionally, the establishment of the shared key and the mutual authentication is simultaneously done between the cloud servers and DRs. Findings: The proposed scheme can achieve forward secrecy by adopting the bloom filter technique that efficiently helps the updating of a private key with no need for the key distributor to reissue the key. The security proof illustrates that this scheme adheres to the security model. Besides, the performance evaluation expresses the feasibility of the suggested scheme. Originality/value: The main goal of designing a puncture algorithm is to devise an updated key from the ciphertext and a secret key, allowing the decryption of all ciphertexts except the one that has been punctured on. This research illustrates the first effort to develop a puncturable attribute-based encryption scheme to achieve efficient finegrained data sharing in IoMRT.